PELANGGARAN INEWS SIANG RCTI DAN LIPUTAN 6 SCTV TERHADAP ATURAN KOMISI PENYIARAN NOMOR 12 TAHUN 2020 - Ramdani, Alwan Husni; Dyanti, Salma Hanifah (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2022)
The Covid 19 pandemic also created an infodemic phenomenon that made the existence of reliable sources of information such as television as a mass media very important. This research focuses on news programs as one of the containers of information in television and its correlation to the state of the Covid 19 virus. The rules on Covid 19 for television itself are covered by the Central Broadcasting Commission Decree No. 12 of 2020. Based on the rule accompanied by the theory of mass media and the Law of the Republic of Indonesia No. 32 of 2002 on Broadcasting, researchers created six analysis units used to detect violations in two news programs, namely Seputar Inews Siang RCTI and Liputan6 SCTV. The method used is quantitative content analysis by making observations to the second episode of the program from April 5, 2021 to April 11, 2021. It found that there was still a violation of more than one analysis unit for both programs with mutual violations in the form of the absence of information related to sterilization and health protocols by all parties involved in the production process.